TERAPI TAWA TERHADAP PENURUNAN TINGKAT STRES AKADEMIK PADA MAHASISWA STRATA 1 - Sulfiani Juhamzah; Widyastuti widyastuti; Ahmad Ridfah (Universitas Negeri Makassar, 2018)
Students are future leaders who are expected to have academic success as their primary goal. However, academic demands can lead to students experiencing academic stress.This study aims to determine the effect of laughter therapy on reducing stress levels in students. Research subjects amounted to (N = 10), which is a force of 2015 that fall into the category of high and medium stress. The researchers used the experimental design of the one group pretest-posttest design using a double pretest. The measuring tool used is the scale of academic stress. Reliability of the measuring scale by calculating the Cronbach Alpha coefficient with a value of 0.822 which signifies high reliability. This research uses Friedman Test data analysis technique that is processed with SPSS version 22. The results showed that the value of Asymp. Sig. 0.000 then 0.000 <0,01, so there is influence of laughter therapy which is very significant to decrease level of academic stress in student of Strata 1 Faculty of Psychology Universitas Negeri Makassar. This study provides a new alternative to the decrease of academic stress level in the students.